Evaluation of the Zoning System Policy in Admission of New Students at the High School Level in Tanah Datar Regency - Sufani Yetra; Ramalis Hakim (Postgraduate School, Universitas Negeri Padang, 2022)
The zoning system in the Admission of New Students is one of the government's breakthroughs that aims to equalize education. However, in reality, there are still many people who complain about this system. This study aims to measure the results or impact of the zoning system with the planned objectives. This research is evaluative research that uses a mixed method and uses the CIPP model. Based on the results of the data analysis, the researchers found a conclusion. First, in terms of context, the distribution of education is significantly less visible. Second, in terms of input, the schedule for implementing the zoning system is by the government's recommendation, but the guidelines and registration requirements are still complicated and infrastructure has not been fulfilled evenly. Third, in terms of process, in the learning process teachers and students are faced with mixing weak and smart students in one class, so they must support each other so that there is no discrimination in class. Fourth, in terms of product, the results of the implementation of the zoning system may have evened out the distribution of students, but there are still many other technical matters that need to be addressed first to create an equal distribution of education without reducing the quality of education itself.